2021
DOI: 10.3389/fimmu.2021.699746
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Harnessing TRAIL-Induced Apoptosis Pathway for Cancer Immunotherapy and Associated Challenges

Abstract: The immune cytokine tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) has attracted rapidly evolving attention as a cancer treatment modality because of its competence to selectively eliminate tumor cells without instigating toxicity in vivo. TRAIL has revealed encouraging promise in preclinical reports in animal models as a cancer treatment option; however, the foremost constraint of the TRAIL therapy is the advancement of TRAIL resistance through a myriad of mechanisms in tumor cells. Investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 231 publications
(160 reference statements)
0
26
0
Order By: Relevance
“…We, here, provided important insights into: (1) the role played by the non-apoptotic pathways induced by TRAIL in the resistance of this model to the DR5-agonist AMG655; (2) the validation of TRAIL-based therapies in pediatric bone tumors; and (3) the proof of concept for new adjuvant targets that can synergize with TRAIL receptors agonists. Several synergies have already been described in the literature [ 40 ], here we can suggest, for example, Necrostatine-1 that inhibits RIPK1 kinase activity [ 41 , 42 ]. This compound has already demonstrated therapeutic interest thanks to its ability to inhibit TRAIL-induced necroptosis by acidic pH in liver and colon cancer cell lines [ 43 ].…”
Section: Discussionmentioning
confidence: 72%
“…We, here, provided important insights into: (1) the role played by the non-apoptotic pathways induced by TRAIL in the resistance of this model to the DR5-agonist AMG655; (2) the validation of TRAIL-based therapies in pediatric bone tumors; and (3) the proof of concept for new adjuvant targets that can synergize with TRAIL receptors agonists. Several synergies have already been described in the literature [ 40 ], here we can suggest, for example, Necrostatine-1 that inhibits RIPK1 kinase activity [ 41 , 42 ]. This compound has already demonstrated therapeutic interest thanks to its ability to inhibit TRAIL-induced necroptosis by acidic pH in liver and colon cancer cell lines [ 43 ].…”
Section: Discussionmentioning
confidence: 72%
“…Functioning as one of the tumor necrosis factor ligand family, TRAIL has been reported to induce apoptosis in tumor cells preferentially. Recent studies have reported that targeting TRAIL is a promising anticancer therapy for prostate cancer, and harnessing TRAIL-induced apoptosis pathway for immunotherapy has attracted attention rapidly as a cancer treatment target ( 27 , 28 ). However, the existing reports on TRAIL are focusing on the function of tumor cell apoptosis induction, and no study on diagnostic biomarker value for PCa has been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…As TRAIL induces apoptosis of tumor cells by triggering DRs, the sensitivity of tumor cells to TRAIL is usually proportional to the level of DRs expressed on these cells (Wong, 2011 ; Di et al., 2013 ; Razeghian et al., 2021 ). In fact, COLO205 cells expressed more DR4 and DR5 than HT29 cells ( Figure 1(B) ).…”
Section: Discussionmentioning
confidence: 99%